Introduction - Lund, Jacob; Sejten, Anne (The Nordic Journal of Aesthetics, 2018)
Across philosophical traditions the question of taste has – at least paradigmatically since Kant’s third critique – been one of the most, perhaps the most central question within the discipline of aesthetics. The present issue of NJA explores ways in which this question can be addressed today; politically, analytically, historically, disciplinarily. The articles all stem from the inaugural conference of the research network Aesthetics Unlimited, which was held at Roskilde University, Denmark on 4–5 May 2017. Collaborating with Séminaire d’Esthétique Européen this new international research network for aesthetic studies is funded by the Danish Council for Independent Research and is led by Anne Elisabeth Sejten, Professor of Aesthetics at Roskilde University.